Positive neurologic outcome in a child after in-hospital cardiac arrest - L. D. Tantsiura; I. V. Kyselova; A. V. Biliaiev; V. V. Orel; M. V. Trykash; V. M. Skliar; I. M. Kolosova (Zaporožskij Medicinskij Žurnal)
The case of positive neurologic outcome in a child after in-hospital cardiac arrest is presented in the article. Factors influencing the survival and neurologic outcome following CPR in children are analysed. Literature data on the differences in outcomes after out-of-hospital and in-hospital cardiac arrest are given.